How costly is financial constraint ? - Ek, Chanbora (2016)
Financial constraint is a status of a firm when the firm's actual capital stock is lower than its desired capital stock – the capital stock level the firm would have chosen in the absence of financial frictions. Financial constraint occurs when the cost of raising external funds is higher than the cost of internal funds (cost constraint) or when there are limits on how much firms can raise external funds (quantity constraint). Under a perfect capital market, real investment decision is independent of financial status. In an imperfect capital market, various financial frictions break down this independence and finance becomes an important determinant of firm investment and productivity. As a result, we expect financial frictions to play significant roles in governing the performance of individual firms and of the economy as a whole. Using firm-level datasets and employing newly-developed microeconometric techniques, this thesis investigates three interesting implications of financial constraint on investment and productivity. First, how to determine whether a firm is financially constrained and the effect of financial constraint on firm-level investment; second, how to quantify the impact of financial frictions on the aggregate productivity loss of the economy as a whole through capital misallocation; and third, how to detect whether financial constraint affects the productivity of individual firms endogenously. Chapter 1 provides motivation of this thesis, together with general reviews of related literatures on financial constraint. Chapter 2 investigates empirically the most controversial, yet influential, measure of financial constraint –investment-cash flow sensitivity– using firm-level datasets of U.S. and China. Under a perfect capital market, investment decision is independent of a firm's financial status. Therefore investment will not exhibit any sensitivity to cash flow when investment opportunities are properly controlled for. Imperfections in the capital market, however, can cause a wedge between the cost of internal and external finance. Therefore investment will respond positively to the availability of cash flow if a firm is financially constrained. As a benchmark, this model is applied to a panel of U.S. manufacturing firms, which we expect to be not/little constrained, and a panel of Chinese manufacturing, which we expect to be constrained. We also apply the model on different groups of Chinese firms. Our results consistently support: 1. the hypothesis that at least some of the Chinese firms are financially constrained; 2. the evidence from the data that there is a capital misallocation in China; and 3. the idea that more productive firms are generally more constrained. Chapter 3 examines capital misallocation within China. Capital misallocation exists when firms have different marginal revenue product of capital (MRPK). This dispersion of MRPK across firms can be due to financial friction or policy distortion. Financial friction in capital misallocation means that although a firm has a high MRPK compared to another firm, this firm cannot increase its capital investment to take advantage of its high MRPK at all, since it needs to raise the necessary fund externally, and since its financial status is viewed by potential investors or lenders as not desirable. On the other hand, even though two firms have identical financial status, they might still receive different treatment with regard to the rate of return or interest rate required by investors or lenders. We call this kind of distortion "policy distortion". The main contribution of this chapter is to disentangle the effect of policy distortion and financial friction in explaining the difference in MRPK across different groups of firms, using a propensity score matching. We find that financial frictions cause an 8.6% total factor productivity loss, which accounts about 30% of the overall loss. While Chapter 2 and 3 take the firm-level productivity as exogenous, Chapter 4 studies whether financial constraint may affect a firm's productivity endogenously. Though there are many studies on the effect of finance on firm's investment, how financial constraint affects firm's productivity, which is a prominent factor for a firm's performance and a country's economic growth, has not received much attention. In addition, those few studies on this linkage have often not been able to produce reliable results due to econometric issues involved. More specifically, the so-called two-stage approach first estimates firm's productivity using production-function-estimation approaches such as Olley and Pakes (1996), Levinsohn and Petrin (2003), and Ackerberg, Caves, and Frazer (2006), with exogenous productivity process, then uses this newly generated productivity to regress on various financial variables to identify financial effects on productivity. However, if finance does affect productivity, not-including financial variables as regressors in the productivity process would lead to biased and inconsistent estimates of production function parameters as well as inconsistent estimation of productivity. We attempt to resolve this issue by augmenting various measures of financial constraint directly into the proxy function and the second-stage productivity regression under the Ackerberg, Caves, and Frazer (2006) approach. Chapter 5 summarizes our results and contributions. We also discuss various potential future researches related to the thesis.